2012
DOI: 10.1002/asia.201200428
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Amino Acid Functionalized Tripodal Hexaamide Anion Receptors: Ion‐Pair‐Assisted Capped‐Cleft Formation by a Pentafluorophenyl‐Functionalized Amide

Abstract: A new series of tris(2‐aminoethyl)amine (tren)‐based L‐alanine amino acid backboned tripodal hexaamide receptors (L1–L5) with various attached moieties based on electron‐withdrawing fluoro groups and lipophilicity have been synthesized and characterized. Detailed binding studies of L1–L5 with different anions, such as halides (F−, Cl−, Br−, and I−) and oxyanions (AcO−, BzO− (Bz=benzoyl), NO3−, H2PO4−, and HSO4−), have been carried out by isothermal titration calorimetric (ITC) experiments in acetonitrile/dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Tren based L-alanine amino acid backboned electronwithdrawing group attached hexa-amide receptors 43-47 (Chart 12) are explored by our group towards anion binding. 91 Appreciable binding between receptors and Cl À , AcO À , BzO À , and HSO evidence of a Cl À complex of the pentafluorophenyl attached receptor 43 shows the formation of Cl À encapsulated unimolecular capsule (Fig. 20).…”
Section: Anion Binding In Unimolecular Capsulesmentioning
confidence: 99%
“…Tren based L-alanine amino acid backboned electronwithdrawing group attached hexa-amide receptors 43-47 (Chart 12) are explored by our group towards anion binding. 91 Appreciable binding between receptors and Cl À , AcO À , BzO À , and HSO evidence of a Cl À complex of the pentafluorophenyl attached receptor 43 shows the formation of Cl À encapsulated unimolecular capsule (Fig. 20).…”
Section: Anion Binding In Unimolecular Capsulesmentioning
confidence: 99%
“…Besides that, tris (2‐amino‐ethyl) amine (tren) is another most used scaffold for the design of three‐dimensional receptors. By attachment of functional groups to the tren unit to modify the binding sites and even the receptors’ conformation, those acyclic tripodal receptors have been reported to exhibit specific binding ability towards different types of guests, such as tetrahedral oxoanions (NO 3 − , PO 4 3− and SO 4 2− ), halide ions (F − and Cl − ), divalent oxalate (C 2 O 4 2− ), and metal ions (Cu 2+ and Hg 2+ ) . Until now, the exploration of tripodal ligands for nucleoside polyphosphates recognition is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…This tripodal structure has proven to be a promising scaffold for anion binding due to its favorable conformation for multiple hydrogen bonds, and many tren-based receptors with a variety of anion-binding sites such as amine, amide, urea, and thiourea groups, etc. have been synthesized. Such receptors not only can complementarily encapsulate oxoanions (sulfate, carbonate, and phosphate) but also display excellent binding abilities to the spherical halide ions. For instance, Beer et al reported that a tripodal tris(amido-benzo-15-crown-5) ligand can cooperatively bind chloride, iodide, or perrhenate anions, while Fabbrizzi et al studied the incipient and definitive proton transfer of urea-fluoride interaction with tripodal ligands.…”
Section: Introductionmentioning
confidence: 99%